Dapagliflozin once daily plus exenatide once weekly in obese adults without diabetes: Sustained reductions in body weight, glycaemia and blood pressure over 1 year. Issue 9 (31st May 2017) - Lundkvist, Per; Pereira, Maria J.; Katsogiannos, Petros; Sjöström, C. David; Johnsson, Eva; Eriksson, Jan W.
Abstract : Aims: Dapagliflozin and exenatide reduce body weight by differing mechanisms. Dual therapy with these agents reduces body weight, adipose tissue volume, glycaemia and systolic blood pressure (SBP) over 24 weeks. Here, we examined these effects over 1 year in obese adults without diabetes. Materials and methods: Obese adults without diabetes (N = 50; aged 18‐70 years; body mass index, 30‐45 kg/m 2 ) were initially randomized to double‐blind oral dapagliflozin 10 mg once daily plus subcutaneous long‐acting exenatide 2 mg once weekly or to placebo. They entered an open‐label extension from 24 to 52 weeks during which all participants received active treatment. Results: Of the original 25 dapagliflozin + exenatide‐treated and 25 placebo‐treated participants, respectively, 21 (84%) and 17 (68%) entered the open‐label period and 16 (64%) and 17 (68%) completed 52 weeks of treatment. At baseline, mean body weight was 104.6 kg, and 73.5% of participants had prediabetes (impaired fasting glucose or impaired glucose tolerance). Reductions with dapagliflozin + exenatide at 24 weeks were sustained at 52 weeks, respectively, for body weight (−4.5 and −5.7 kg), total adipose tissue volume (−3.8 and −5.3 L), proportion with prediabetes (34.8% and 35.3%), and SBP (−9.8 and −12.0 mm Hg). Effects on body weight, SBP and glycaemia at 52 weeks with placebo → dapagliflozin + exenatide were similar to those observed with continuation of dapagliflozin + exenatide. Nausea and injection‐site reactions were more frequent with dapagliflozin + exenatide than with placebo and diminished over time. Safety and tolerability were similar to that in previous diabetes trials with these agents. No clear difference in adverse event‐related withdrawals between placebo and active treatment periods was observed. Conclusions: Dapagliflozin + exenatide dual therapy produced sustained reductions in body weight, prediabetes and SBP over 52 weeks and was well tolerated in obese adults without diabetes.